back Design And Construction Of A Web-Based Furniture Sales Information System For Order Management And Goods Delivery Monitoring - Sendi Farera Adi Gunawan (Jurnal Media Computer Science, 2026)
Technology has become the lifeblood of many businesses, enabling them to transform digitally to improve business effectiveness. Offo Living Solo is a furniture company facing challenges in product management, ordering, and transaction recording, particularly related systems, which still require manual procedures. This research aims to design and build a web-based furniture sales information system that effectively integrates business processes and provides user convenience. The system development method used is the Waterfall method, which consists of the stages of needs analysis, design, implementation, testing, and maintenance. The developed system features product catalog management by category, special orders, shopping carts, checkouts, payments, automated stock management, order management, real-time delivery tracking, and sales report preparation. System testing was conducted using the Black Box Testing method to ensure each function runs according to the designed requirements and specifications. The test results showed that all key system features functioned well, thus improving operational efficiency, reducing recording errors, accelerating service processes, and increasing information transparency to customers. Thus, the developed web-based furniture sales information system can be implemented as a digital solution to support Offo Living Solo's business management and enhance business competitiveness in the digital era.